Welfare of cattle kept in intensive silvopastoral systems: A case report - Tarazona Morales, Ariel Marcel; Ceballos, Maria Camila [UNESP]; Correa Londono, Guillermo; Cuartas Cardona, Cesar Augusto; Naranjo Ramirez, Juan Fernando; Rodrigues Paranhos da Costa, Mateus Jose [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2017)
The objective of this research was to evaluate the effect of three different intensive silvopastoral systems (ISPS) on cattle animal welfare (AW) in Colombia. The three ISPS differed in area, plant composition, and grazing periods as follows: ISPS1 - low plant diversity in paddocks of 1200 m(2), with grazing period of 24 h; ISPS2 - middle plant diversity in paddocks of 600 m(2), with grazing period of 12 h; and ISPS3 - high plant diversity in paddocks of 600 m(2), with grazing period of 24 h. Animal welfare was assessed using a wide range of criteria, which were integrated using L-spline functions and Choquet integrals to generate overall values. It was found that AW was good in all ISPS; the highest scoring criteria was for food and water, with 99, 97, and 100 points from a maximum of 100 for ISPSs 1, 2, and 3, respectively. Comfort showed values of 100 for all three systems, but good health was the most problematic criteria of the AW features with scores of 25, 40, and 36 for ISPSs 1, 2, and 3, respectively. All three ISPS showed excellent scores for appropriate behavior (82, 88, and 89). The welfare problems shown here were not specific to the individual ISPS, but were common to all livestock systems in the region. Despite the differences in diversity of plants, size of paddocks, and grazing period among the three ISPSs tested, all of them provide cattle with sufficient resources and a diverse environment, ensuring a good state of welfare to them.
Keywords: animal emotion; animal welfare; appropriate behavior; livestock; sustainability